Sectoral Resilience of Enterprises in Eastern Nepal Amid Covid-19 with Reference to Young Entrepreneurs - Rai, Arjun; Rai, Chandra Kumar (Researcher: A Research Journal of Culture and Society, 2021)
This investigation compared the negative effect of the Covid-19 pandemic on different business sectors run by young entrepreneurs from eastern Nepal. The population in this study comprised all the young entrepreneurs of eastern Nepal. A standardized instrument was used to collect primary data from 204 young entrepreneurs. An independent sample t-test and Analysis of Variance were used as statistical tools to compare the negative impact of Covid-19 on different sectors of business. The collected data were coded, entered, and processed in Statistical Package for the Social Science (SPSS), version 25. The results of the study revealed that different sectors of businesses were negatively and significantly affected by Covid-19. The grocery business was the least negatively affected business amongst the seven sectors included in this study.